2018
DOI: 10.1542/peds.2018-0449
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Resective Epilepsy Surgery in Patients With Lennox-Gastaut Syndrome

Abstract: Resective surgery is a viable option in some patients to treat seizures that are associated with LGS, with a high probability of seizure control and better adaptive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 24 publications
(18 reference statements)
4
41
0
Order By: Relevance
“…The finding that cortical involvement precedes thalamic participation in GPFA is consistent with our recent DCM analysis of EEG‐fMRI in LGS, 4 which found that GPFA was more likely to be initiated by prefrontal cortex than either thalamus or brain stem. It is also consistent with our prior single photon emission computed tomography study of tonic seizures showing early blood flow changes in prefrontal cortex and the pontine region of the brain stem, 16 and the known phenomenon that cortical lesions can cause LGS, whereas their removal can abolish seizures 5,17 . Given our findings of widespread scalp EEG changes at GPFA onset, prior to thalamic involvement, it appears that mechanisms apart from the thalamus may be responsible for initiating epileptic activity across diffuse cortical regions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding that cortical involvement precedes thalamic participation in GPFA is consistent with our recent DCM analysis of EEG‐fMRI in LGS, 4 which found that GPFA was more likely to be initiated by prefrontal cortex than either thalamus or brain stem. It is also consistent with our prior single photon emission computed tomography study of tonic seizures showing early blood flow changes in prefrontal cortex and the pontine region of the brain stem, 16 and the known phenomenon that cortical lesions can cause LGS, whereas their removal can abolish seizures 5,17 . Given our findings of widespread scalp EEG changes at GPFA onset, prior to thalamic involvement, it appears that mechanisms apart from the thalamus may be responsible for initiating epileptic activity across diffuse cortical regions.…”
Section: Discussionsupporting
confidence: 91%
“…It is also consistent with our prior single photon emission computed tomography study of tonic seizures showing early blood flow changes in prefrontal cortex and the pontine region of the brain stem, 16 and the known phenomenon that cortical lesions can cause LGS, whereas their removal can abolish seizures. 5,17 Given our findings of We did not find an effect of "pathway" (ie, different pairs of scalp and thalamic electrode contacts) on PTE values, nor an interaction between brain state and pathway.…”
Section: Discussionmentioning
confidence: 50%
“…Resective surgery is a treatment option in LGS patients with focal pathology and there is a high probability of seizure control in about 50% of patients following surgery 32 . Patients are carefully identified for resective surgery based on congruent findings of a definitive structural lesion using electroencephalogram (EEG), magnetic resonance imaging (MRI), and functional neuroimaging.…”
Section: Discussionmentioning
confidence: 99%
“…38 Among resective surgery studies, shorter duration of preoperative epilepsy and hemispherectomy were associated with better seizure outcomes. 21,66 53 Common measures included parental or caregiver rating, 56,59,63 Weschler Intelligence Scale for Children, 53,61,65 and visual analogue scale. 56,61 Five studies 29,36,54,59,64 noted specific improvements in alertness for a majority of their LGS patients after VNS.…”
Section: Prognostic Factorsmentioning
confidence: 99%